حسن أيوب وجهوده الفكرية من خلال مؤلفاته - ميسة, إيمان; بالعيد, أميرة; ولابي, سناء; محيدة, هناء (جامعة الوادي university of eloued, 2020)
قمنا في هذا البحث بدراسة حياة الشيخ حسن أيوب رحمه الله ) 1918 م- 2008 م ( منذ ولادته إلى وفاته ، و ذكر أهم مؤلفاته في العلوم المختلفة ، ثم قمنا بدراسة هذه المؤلفات و تحليلها و استخراج أهم الأفكار التي جسدها الشيخ حسن أيوب رحمه الله فيها من أمور دينية كالعقيدة و الفقه ، و أمور دنيوية من تاريخ و سياسة و غيرها ، و قد واضح في مؤلفاته أنه ذا عقيدة وسطية و فقه مرن ميسر فتباعد عن غلو السلفية المتطرفة فسلك طريقا وسطا يسير فيه بنور القرآن الكريم و سنة نبيه . Summary In this research, we studied the life of Sheikh Hassan Ayoub, may God have mercy on him (1918 AD -2008 AD) from his birth to his death, and mentioned his most important books in various sciences, then we studied these books and analyzed them and extracted the most important ideas embodied by Sheikh Hassan Ayoub, may God have mercy on him. Religious matters such as doctrine and jurisprudence, and worldly matters from history, politics, etc., and it has been clear in his writings that he has a moderate doctrine and a flexible and facilitated jurisprudence, so he diverges from the extremism of extremist Salafism, so he follows a middle path in which he walks with the light of the Holy Qur’an and the Sunnah of his Prophet.
دعوة